Language Change in Epic Greek and Other Poetic Traditions - Beek, Lucien van, (Language and Linguistics E-Books Online, Collection 2025., 2025)
Homeric language fascinates because of its many oddities with respect to other forms of Ancient Greek. From which dialects did this poetic language take shape and develop? In which ways did individual poets alter the language? In this volume you will find twelve cutting-edge studies on linguistic change in oral traditions, with a focus on Early Greek epic but also including Near-Eastern traditions (Biblical Hebrew, Quranic Arabic). Several studies focus on an innovative idea of phonological change occurring within an oral tradition. You will also find studies on the adaptation of linguistic form to meter; formulae and epithets; and contact between different traditions or registers.